The Forecasting Approach to Efficiency in the Wool Market - Barry Goss (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1989)
This paper develops and presents estimates of a simultaneous equations model of the Australian wool market, the world's largest producer and exporter of fine wool.
Keywords: 330